The Efficiency of Investing in Open-End Mutual Funds in Poland in Years 2001–2010 - Jurek-Wasilewska, Kinga (Journal of Finance and Financial Law, 2014)
The article aims to evaluate the efficiency of investing in units of open-end mutual funds in Poland using rate of return and risk-adjusted ratios derived from the Capital Asset Pricing Model. The analysis was based on the statistical verification of the quality of asset management in relation to the market portfolio performance in various market conditions. The survey included open-end mutual funds divided into groups according to their investment policy in years 2001–2010. The results of the evaluation process revealed that in the face of changing market conditions the efficiency of mutual funds performance, regardless of their investment policies, was not significantly different or significantly worse than the results of the passive market portfolio. This phenomenon might be caused by possible lack of knowledge, information and skills of the fund managers or unreliable tools they were using.